Exploring the Anxiolytic Potential of NPY by a Dipeptidyl Peptidase-IV Inhibitor in an Animal Model of PTSD - Dahan, Matan; Zohar, Joseph; Todder, Doron; Mathé, Aleksander A; Cohen, Hagit (The international journal of neuropsychopharmacology, 2024)
Abstract Background The regulatory neuropeptide Y (NPY) is implicated in anxiety and post-traumatic stress disorder (PTSD)-related behaviors. NPY exerts its effects through 5 receptor subtypes, with Y1 and Y2 receptors being predominantly expressed in the rat brain. Activation of Y1 by full-length NPY1-36 induces anxiolytic effects, whereas Y2 binds truncated peptides, eliciting region-specific anxiogenic responses. Dipeptidyl peptidase-IV (DPP-IV) cleaves NPY, thereby modulating its functionality. Sitagliptin, a DPP-IV inhibitor (DPP-IV-I), inhibits the degradation of various vasoactive peptides, including cerebral NPY. As such, the therapeutic potential of DPP-IV-I following a traumatic event remains inconclusive. We assessed the effects of a highly selective DPP-IV-I, administered either shortly after the stressor or intermittently over 3 days, on behavioral outcomes using the predator scent stress (PSS) model of PTSD. Methods Rats exposed to PSS or sham-PSS received a single dose of sitagliptin (10 or 30 mg/kg) or saline 1 hour post-exposure, or repeated doses over 3 days (20 mg/kg). Behavioral outcomes were evaluated using the elevated plus maze and acoustic startle response at 7 days post-exposure. Additionally, rats exposed to PSS or sham-PSS were treated with sitagliptin (30 mg/kg) or saline, and their brains were prepared for immunofluorescence and enzyme-linked immunosorbent assay (ELISA). Results Sitagliptin did not attenuate anxiety-related behaviors or PTSD-related behavior prevalence compared to saline. Notably, the 30 mg/kg dose increased NPY levels in several brain regions without affecting NPY-Y1 levels. Conclusions The findings suggest that sitagliptin-induced upregulation of NPY levels shortly after PSS is insufficient to prevent the development of post-traumatic responses. The effectiveness of NPY signaling may be influenced by factors beyond peptide concentration alone, potentially limiting its therapeutic efficacy. Activation of NPY-Y1 receptors, rather than merely increasing NPY levels, appears to be crucial for modulating anti-anxiety and post-traumatic responses.